Effect of post-oxidation processes and thickness of SnO2 films prepared by vacuum evaporation on CO gas sensing characteristics. Issue 9 (1st May 2021) - Mauraya, Amit Kumar; Singh, Preetam; Muthiah, Saravanan; Kushvaha, Sunil Singh; Muthusamy, Senthil Kumar
Abstract: This report discusses the effect of post-oxidation processes and thickness of SnO2 thin films on their physical properties and CO gas sensing characteristics. SnO2 films have been grown by simple vacuum evaporation of Sn metal and post-oxidation process. The post-oxidation of Sn films was performed by two different methods, i.e., step-oxidation and direct-oxidation, at a maximum temperature of 850 °C. The thickness of Sn films was varied as 100, 200 and 500 nm. As characterized by x-ray diffraction technique, the SnO2 thin films have a tetragonal rutile structure with crystallite size of 21 and 27 nm for direct-oxidation and step-oxidation methods, respectively. The SnO2 films produced by both oxidation methods possess a porous, granular surface morphology as revealed by scanning electron microscopy. The band gap of SnO2 films calculated using ultraviolet–visible spectroscopy in absorption mode is found to be in the range of 3.36–3.59 eV. The CO sensing performance has been examined at various measurement temperatures up to 400 °C using calibrated CO gas. It is found that the CO sensitivity is significantly higher for the direct-oxidized SnO2 films as compared to the step-oxidized films. Also, thinner SnO2 film, i.e. 100 nm of thickness, obtained by direct-oxidation method is found to have the highest sensitivity of 70.7% against CO gas of 915 ppm concentration with a fast response time of 21 s. The effective CO sensing of thinner SnO2 film is understood based on the formation of smaller grains with the uniform surface distribution. The film is more selective towards CO gas as compared to NH3 and NO2 gases and shows a CO limit-of-detection of 10 ppm.